2013
DOI: 10.1088/0953-8984/25/8/086002
|View full text |Cite
|
Sign up to set email alerts
|

Switching the in-plane easy axis by ion implantation in rare earth based magnetic films

Abstract: Ar(+) ions have been implanted into Laves phase epitaxial thin films of YFe(2) and DyFe(2). Magneto-optical Kerr effect and vibrating sample magnetometry experiments show that the easy and hard axes of magnetization in both materials rotate through an in-plane angle of 90°, whilst the strength of the magnetic anisotropy remains unaltered. This is supported by OOMMF computational modelling. Atomic force microscopy confirms that the film roughness is not affected by implanted ions. X-ray diffraction data show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To get numerical values, we need to specify the magnetic parameters. The magnetic parameters in the two regions should be different to get sizable energy gaps, which can be realized by ion implantation 12,13 or using artificial superlattices 36,37 . However, it should be noted that, in contrast to conventional 1D MCs, DWMCs have energy gaps even if regions 1 and 2 have the same set of magnetic parameters (cf.…”
Section: Band Structure Of Domain-wall Magnonic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get numerical values, we need to specify the magnetic parameters. The magnetic parameters in the two regions should be different to get sizable energy gaps, which can be realized by ion implantation 12,13 or using artificial superlattices 36,37 . However, it should be noted that, in contrast to conventional 1D MCs, DWMCs have energy gaps even if regions 1 and 2 have the same set of magnetic parameters (cf.…”
Section: Band Structure Of Domain-wall Magnonic Crystalsmentioning
confidence: 99%
“…The magnetic materials in the two regions could be identical or different. For a usual MC, in order to induce an energy gap for SWs, the magnetic parameters of the two regions have to be different, which can be realized by using different materials or local modification of the magnetic properties of the same material through ion implantation 12,13 . In our simplified 1D treatment of DWMCs, what matters is the magnetic parameters in the two regions, which are differentiated by the subscripts 1 and 2 for regions 1 and 2, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The direction of easy magnetization of the RE-Fe 2 compounds is determined by the magnetocrystalline anisotropy associated with RE 3 þ ions [9]. It has been demonstrated that the magnetic anisotropy of the RE-Fe 2 films, as a basic role playing in the magnetic reversal process, can be modified by ion irradiation or patterning [10]. By patterning epitaxial 400-nmthick RE-Fe 2 films into micro-sized stripes shape anisotropy in the order of 10 5 erg/cm 3 in magnitude can be created [11][12][13].…”
Section: Introductionmentioning
confidence: 99%